2007
DOI: 10.1243/09576509jpe374
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the effect of sweep on the performance and flow field in an axial flow compressor rotor

Abstract: In the recent past, experimental studies have shown some advantages of blade lean and sweep in axial compressors. As most of the experimental results are combined with other features, it is difficult to determine the effect of individual parameters on the performance of the compressor. The present numerical studies are aimed at understanding the performance and three-dimensional flow pattern within and at the exit of swept and unswept rotors. Three rotors, namely, unswept, 20° forward swept, and 20° backward s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 16 publications
4
21
0
Order By: Relevance
“…At tip regions, unswept rotor is found to produce more pressure rise. This observation is similar to the one reported by Govardhan, Krishnakumar and Sitaram (2007). This difference in the pressure rise as well as the span over which the unswept rotor produced more pressure rise from the tip are found to increase with the introduction of τ/ch = 0.007 clearance.…”
Section: Relative Stagnation Pressure Loss Coefficient (Y R )supporting
confidence: 90%
“…At tip regions, unswept rotor is found to produce more pressure rise. This observation is similar to the one reported by Govardhan, Krishnakumar and Sitaram (2007). This difference in the pressure rise as well as the span over which the unswept rotor produced more pressure rise from the tip are found to increase with the introduction of τ/ch = 0.007 clearance.…”
Section: Relative Stagnation Pressure Loss Coefficient (Y R )supporting
confidence: 90%
“…Theories based on infinite span blades would invariably be different in such cases. Streamline twist [8,9] and spanwise redistribution of flow [4,7] are reported with sweep in such low aspect ratio configurations. Starting from lifting line theory, nearly all the blade design procedures (axisymmetric flow assumption followed by finding a blade-to-blade solution for each axisymmetric stream surface) are not legitimate when the blades are swept.…”
Section: Introductionmentioning
confidence: 93%
“…Based on the results from the literature [4][5][6]13], it was contemplated that better 3D stacking scheme would be the combination of forward tip chordline sweeping and positive dihedral, which turns out to be "axial sweeping". Thus, the 3D blade stacking schemes chosen for the present study are shown in Table 1.…”
Section: Sweep Configurationsmentioning
confidence: 99%
See 2 more Smart Citations